2017
DOI: 10.1016/j.ejphar.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Probucol attenuates lipopolysaccharide-induced leukocyte recruitment and inflammatory hyperalgesia: effect on NF-кB activation and cytokine production

Abstract: Probucol 4,4'- (Isopropylidenedithio)bis(2,6-di-tert-butylphenol) is a synthetic molecule clinically used for prevention and treatment of hypercholesterolemia and atherosclerosis. Recent studies have shown that the beneficial effects of probucol mainly derive from its anti-inflammatory and antioxidant properties. Gram-negative bacteria are common infectious agents and their wall components, e.g. lipopolysaccharide (LPS), are important elicitors of inflammation. LPS is sensed by tissue resident cells and it tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 66 publications
1
19
1
Order By: Relevance
“…Increasing evidence has shown that probucol can effectively reduce inflammation by inhibiting the NF-κB pathway and reducing the release of inflammatory cytokines, such as TNF-α. 16 17 18 …”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that probucol can effectively reduce inflammation by inhibiting the NF-κB pathway and reducing the release of inflammatory cytokines, such as TNF-α. 16 17 18 …”
Section: Discussionmentioning
confidence: 99%
“…injected daily with PF (≥98% purity by HPLC analysis, P0038, Sigma–Aldrich, St. Louis, MO, USA) or the same volume of sterilized saline (vehicle of PF) continuously for 1 week, separately. Two hours after last injection on the seventh day, LPS (200 ng/20 µL) ( Escherichia coli 0111: B4) (L2630, Sigma–Aldrich) or the same volume of sterilized saline (vehicle of LPS) was injected into the plantar surface of right hind paw using a microsyringe with a 30‐gauge needle, respectively 16 . After 5 h, mice were sacrificed by cervical dislocation and samples were collected for further evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Probucol (Sigma, St. Louis, MO, USA; 30 mg/kg/day) was diluted in carboxymethylcellulose (CMC), 1 mg/mL. The probucol dose was chosen based on previous studies that reported neuroprotective effects of this compound [ 48 50 ]. YAC128 and wild-type (WT) mice were randomly divided into four experimental groups (with equal numbers of males and females included in each group, 10 mice/group): 1 (WT vehicle), 2 (YAC128 vehicle), 3 (WT probucol), and 4 (YAC128 probucol).…”
Section: Methodsmentioning
confidence: 99%